Design and Validation for OE35 mooring system (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This research presents a comprehensive analysis of the mooring system design for the 1MW OE35 wave energy converter, which is being developed by the WEDUSEA project. The study centres on the dynamic analysis of mooring configurations using Orcaflex software to simulate the environmental and operational conditions expected at the deployment site. The analysis involved an iterative design and validation process, refined through both numerical modelling and basin testing. These tank tests were crucial for validating the Orcaflex model outcomes by providing a controlled environment to observe the physical behaviours of the proposed mooring configurations under simulated sea conditions. The finalized mooring system design employs a three-point catenary setup, optimized through extensive simulation to withstand varied environmental loads while maintaining system integrity and device stability. This paper outlines the progression from initial mooring concepts to a thoroughly validated design, demonstrating improvements in mooring strategies that enhance the reliability and performance of wave energy converters in real sea conditions. The findings from this analysis contribute significantly to the ongoing efforts to scale wave energy technologies, aligning with broader industry targets for cost reduction and sustainability in renewable energy deployments.